An Appraisal on Practical Implication of Yogya Sutriya - Rathore, Love krishna Pal Singh; S, Anand (Asian Journal of Pharmaceutical Research and Development, 2022)
Classical references doencapsulate the utility of surgical interventions years ago itself. There was a time with our ancient Acharyas have postulated different treatment modalities and later on these contributions were transmigrated into modern face. Susrutasamhita has put forward a unique notionregarding practical aspects of Shalyaaaharana. Different chapters were described in Sutra sthana, enlightening the same concept and these are more reliable and helpful in clinical practise at present. Yogyasutriya as one among those chapters, explores knowledge on practical training. Various methodologies have been mentioned in this particular chapter. Administration of this in current clinical practise will be more precise and recommended one. Execution of the methods which are explained by Acharya is more important now a days. So apart from a review point of view, a contemporary paradigm is needed with demonstration and pictorial representation too. So that students will be more benefited during their practical phases.